2005
DOI: 10.1523/jneurosci.0850-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Relearning Sound Localization with a New Ear

Abstract: Human sound localization results primarily from the processing of binaural differences in sound level and arrival time for locations in the horizontal plane (azimuth) and of spectral shape cues generated by the head and pinnae for positions in the vertical plane (elevation). The latter mechanism incorporates two processing stages: a spectral-to-spatial mapping stage and a binaural weighting stage that determines the contribution of each ear to perceived elevation as function of sound azimuth. We demonstrated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
132
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 41 publications
(52 reference statements)
13
132
0
Order By: Relevance
“…While there has been no systematic study of what constitutes 'sufficient' residual cues for adaptation, previous studies have shown that retaining some elevation dependent change in spectral features, such as the mid frequency spectral notch or high (8 to 16 kHz) spectral grains, results in accommodation over a period of weeks of exposure to the mould (Hofman et al 1998). Similar mould effects can be seen in van Wanrooij and van Opstal (2005) where the bare ear on one side of the head was compared to the other ear wearing a mould. In the current study, DTFs measured with the moulds in place clearly indicate that elevation-dependent changes remain in the mid frequency notch and the high frequency gain as does a substantial mid frequency gain in the 3 to 6 kHz region (Fig.…”
Section: Acoustic Effects Of the Mouldssupporting
confidence: 57%
See 4 more Smart Citations
“…While there has been no systematic study of what constitutes 'sufficient' residual cues for adaptation, previous studies have shown that retaining some elevation dependent change in spectral features, such as the mid frequency spectral notch or high (8 to 16 kHz) spectral grains, results in accommodation over a period of weeks of exposure to the mould (Hofman et al 1998). Similar mould effects can be seen in van Wanrooij and van Opstal (2005) where the bare ear on one side of the head was compared to the other ear wearing a mould. In the current study, DTFs measured with the moulds in place clearly indicate that elevation-dependent changes remain in the mid frequency notch and the high frequency gain as does a substantial mid frequency gain in the 3 to 6 kHz region (Fig.…”
Section: Acoustic Effects Of the Mouldssupporting
confidence: 57%
“…Previous work has indicated that accommodation does not necessarily proceed in a linear fashion. When a mould was inserted in one ear, Van Wanrooij and van Opstal (2005) reported a sinusoidal pattern in the changes of perceived elevation for the AV region with a period of between 6 and 10 days. While we observed some evidence of nonlinear patterns in some subjects, no clear sinusoidal pattern was evident in any of the performance measures we used here.…”
Section: Patterns Of Accommodationmentioning
confidence: 99%
See 3 more Smart Citations